The Juridical Overview of the Sale of Owned Land on Joint Assets by Husband without Wife's Consent - Ary Patria Wisnu; Nanang Sri Darmadi; Andi Aina Ilmih (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
The purpose of this research is to analyze: 1). The responsibility of the Land Deed Making Officer (PPAT) for the making of the Sale and Purchase Deed of the object of joint property transferred without the wife's approval based on Decision No. 253/Pdt.Plw/2018/PN.Skt. 2). The legal consequences of the sale of land ownership rights to joint property by the husband without the wife's consent based on Decision No. 253/Pdt.Plw/2018/PN.Skt. The approach method in this research is a normative juridical approach. The data used is secondary data obtained through literature study, data analysis was carried out by qualitative analysis. The results of the research concluded: 1). The responsibility of the Land Deed Making Officer (PPAT) for the making of the Sale and Purchase Deed of the object of joint property transferred without the wife's approval based on Decision No. 253/Pdt.Plw/2018/PN. Skt is an absolute responsibility caused because in making the sale and purchase deed the PPAT was not careful and careful. As a result of decision No. 253/Pdt.Plw/2018/PN.Skt is deed No. 112/ sale and purchase deed is contrary to the law, it will cause losses for the opposing party. PPAT must share responsibility for material losses suffered by the parties. 2). The legal consequences of the sale of land ownership rights to joint property by the husband without the wife's consent based on Decision No. 253/Pdt.Plw/2018/PN.Skt is invalid and null and void. As a result, the Plaintiffs suffered material losses. So that in terms of legal certainty theory, this sale and purchase cannot provide legal certainty for the Buyer, so that the Opponent II and PPAT must be responsible for the unlawful acts they have committed.